Hainan province: China's new free trade zone and Hainan medical tourism. (15th November 2019) - Usman, Khalid; Liu, Zhiying; Ping, Chen; Hong, Tangyong; Ming, Hu
The Government of China has promoting the free trade zones of the country to captivate the largest overseas investment. The association between development of tourism and foreign trade is widely recognised. This study discussed the impact of Hainan free trade zone on medical tourism in Hainan province. The Hainan free trade zone plan is not only to promote the growth in South China, but it also contributes to the growth of economy in the Pacific Asia region and the rest of the World. Under the free visa entry policy, the government can attract tourists from all over the world, and can increase the industry of tourism by fulfilling the requirements of international tourists.